Towards a model of Consumer Engagement with Celebrity Brands - Zarkada, Anna K.; Tzoumaka, Eugenia (My University, 2013)
Celebrities are an object as well as an instrument of marketing yet the consumer behaviour literature is focused on brands and organizations as creators of value. Despite the recent academic interest in personal branding there still is no coherent theoretical framework to explain consumer engagement with celebrities. Utilizing a cross-disciplinary review of the psychology, sociology, media, advertising and marketing literature, this paper identifies internal influences on consumer behaviour and proposes a two-dimensional approach to celebrity brands. It contributes to understanding the consumer behaviour mechanisms that elevate celebrities to role models and behaviour or attitude influencers.
Keywords: Celebrities; Branding; Consumers